The perioperative nurses in the elderly cardiac surgery: a systematic review of literature - Avanci, Barbara Soares (2009)
Objective: to perform a systematic review on the role of nurses to elderly patients during the perioperative period of cardiac surgery. Methods: an exploratory study, quantitative and qualitative, held in databases SciELO, MEDLINE, LILACS and BDENF the period 1983 to 2008, where he was selected 15 potential bibliographies. Results: the categories were "need for communication / interaction between nurses and elderly patients before cardiac surgery: discussing the training, "and" role of nurses in the perioperative period of elderly people referred to cardiac surgery: early detection of complications and strategies care. Conclusion: it was felt that the role of perioperative cardiac nurse for the elderly is relevant and embraced by the importance of holding the interaction and communication-old nurse, and that it should be valued and taught at the academy. So, a more effective participation and understanding of nurses, especially in regard to older people who will undergo surgery and even more so when it is open-heart surgery, which will involve mostly a serious nature and a recovery delayed.